Towards a theory-informed practice of entrepreneurship education for university students: the case of HC.LAB - Hahn, Davide; Minola, Tommaso; Cascavilla, Ilaria; Ivaldi, Silvia; Salerno, Mario (Piccola Impresa / Small Business, 2021)
Amongst the various formal and informal mechanismsthrough which a university fosters student entrepreneurship,entrepreneurship education (EE) occupies a centralrole in the academic debate and in university practice.Despite the growing amount of EE studies in the last years,some puzzles persist. More specifically, much remains tobe unveiled on how entrepreneurship should actually betaught in the classroom. Scholars lament a knowledge gapbetween the teaching practices of EE and the theoreticaldevelopment of both the entrepreneurship and the generaleducation fields. To contribute to this debate, this study describesthe characteristics and outcomes of the Healthcare Contamination Lab (HC.LAB), a six-month EE program.In particular, the authors describe a possible way to informthe design of EE with the theoretical foundations of entrepreneurshipand with innovative education principles, usingHC.LAB as a revelatory single case study. More specifically,for five dimensions of EE design, the authors outlinethe originality of the HC.LAB journey and offer some verypreliminary evidence on the results of the first edition of HC.LAB